COPING WITH L2 SOCIOPRAGMATIC SENSITIVITY USING A STORY-BASED APPROACH - Musli Ariani; A. Effendi Kadarisman (Fakultas Sastra Universitas Negeri Malang, 2017)
Abstract: Previous research findings have led to a gap that sociopragmatic failure, instead of pragmalinguistic failure, has scarcely been resolved despite its crucial function in communication. Therefore, this paper proposes a story-based approach, particularly a joint storytelling with multi-party interaction, to deal with learners’ L2 sociopragmatic sensitivity. EFL learners with diverse cultural backgrounds need a motivating environment with agents that can co-construct experiences for optimum learning. By telling stories, learners are engaged in social relations that set them into interpersonal interaction demanding sociopragmatic awareness necessary for the development of their L2 sociopragmatic competence. For this purpose, classroom implementation follows the dimensions of embeddedness, tellership, and tellability while the learning sequence is based on co-constructed learning principles with four stages: setting the stage, executing the storytelling, monitoring the process, and evaluating the results. Future research may be conducted to test the compatibility of the model with actual EFL classroom instructions.permalink/DOI: dx.doi.org/10.17977/um015v45i22017p108